A review of rural transformation studies: Definition, measurement, and indicators - Dong WANG; Chunlai CHEN; Christopher FINDLAY (Journal of Integrative Agriculture)
The paper reviews studies of rural transformation in three dimensions - definition, measurement, and indicators - and summarises the findings of rural transformation research. The scope of rural transformation includes four elements - productivity, rurality, inclusiveness, and sustainability. Current concepts of the dimensions of rural transformation and their associated indicators are insufficient for policy decision-making, as they lack objectivity, feasibility, accountability, comprehensiveness, and comparability. Future research to develop new measures to assess rural transformation in developing countries is valuable. Furthermore, there is potential to explore the topic in some directions: urbanisation strategy, public intervention (i.e., institution, policy, and investment), gender inclusiveness, market creation, and international trade.